The impact of the pandemic on the perception of stress and danger, and the adjustment of psychiatric and general medical staff of German military hospitals - Willmund, Gerd-Dieter; Müller, Johannes; Schneegans, Niels; Höllmer, Helge; Wesemann, Ulrich; Zimmermann, Peter Lutz; Helms, Christian (Frontiers in Psychiatry, 2023)
Introduction The COVID-19 pandemic changed not only the working conditions but also the private conditions we live in. Health care professionals especially were confronted with multiple stressors, e.g., the risk of infection, lack of staff, and high workloads. Methods To estimate some of the pandemic-related impacts this anonymous personnel survey was conducted in two German military hospitals (Hamburg and Berlin). This study presents a comparative analysis of the hospital staff in general vs. the psychiatric personnel (N = 685) at two measurement time points (MTPs) in April 2021 (n = 399) and December 2021 (n = 286). The survey contains the German version of the Covid Stress Scale (CSS) to assess the perceived level of pandemic-related stress, the Patient Health Questionnaire (German Version: PHQ-D) to screen for three major mental disorders, and the adjustment disorder—New Module (ADNM) to estimate the problems of adaptation to change. Results The results showed a process of adaptation over the two MTPs with significant stress reduction at MTP2 in the general staff. The psychiatric staff did not report significantly higher pandemic-related symptoms. Quite the contrary, not only did the CSS show significantly lower xenophobia, traumatic stress, and compulsive checking, but the PHQ also showed lower stress symptoms and somatic symptoms at both MTPs. Also, the ADNM scores delivered evidence for a more effective adaptation process in psychiatric personnel (e.g., depressive mood, avoidance, anxiety). Discussion The presented results must be interpreted while taking the unique situations of German military clinics into account. The supply of protective material was sufficient and there was no dramatic shortage of psychiatric staff during the pandemic. The inpatients were quite often (40%) elective treatments for trauma-related disorders, which could be discontinued in the case of a COVID-19 infection. The results of this study showed good adaptative skills among the psychiatric staff in military hospitals, which could be interpreted as a sign of good resilience. This might have led to lower stress-related symptoms during the COVID-19 pandemic.